Stressors and coping strategies among parents of children with autism spectrum disorder in Ethiopia - Ali Sani Side; R. Sreevalsa Kumar (College of education, Bahir Dar University, 2023)
This study investigated the stressors that parents of children with autism spectrum disorder (PCASD) experienced and the coping strategies they employed to manage it. Following phenomenological design, focused group discussion (FGD) was employed to collect data. Sixteen parents were drawn using purposive sampling participated. Thematic analysis of the data revealed that challenges related to personal development and building friendship, finding schools for children with autism spectrum disorders (CASD), CASD being non-verbal, and the extent of care and safety the CASD need as major stressors for parents. Mothers of CASD experienced more stress compared to their fathers. PCASD used emotion-focused coping strategies. Implications are highlighted against policy formulations and implementation initiatives.